Global Schistosomiasis Database: Practical Considerations in the Design of a User-friendly Database - Yoon, S. S.; Mort, K. E. (Methods of Information in Medicine, 1991)
A computerized database for monitoring global schistosomiasis data is discussed. The potential target users include schistosomiasis program managers, Ministries of Health of endemic countries, consultants, and WHO Regional Offices. The concept behind the design of the database structure, the user interface and the query interface is addressed along with a brief description of the hardware and software used. The database, holding information on 76 schistosomiasis endemic countries around the world, has been tested in the WHO Regional Offices with positive results.
Keywords: Database; Personal Computers; Schistosomiasis; User-interface